2015
DOI: 10.1136/bcr-2014-209076
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for refractory organising pneumonia associated with Sjögren's disease

Abstract: Lung involvement in primary Sjögren syndrome occurs in approximately 10-20% of patients. Tocilizumab, an anti-interleukin-6 receptor antibody, has demonstrated efficacy and safety in small series of systemic sclerosis, and systemic lupus erythematosus, but its effect on interstitial lung manifestations of connective tissue diseases is not well known. We report the use of tocilizumab in a refractory organising pneumonia associated with Sjögren's disease. Our observation suggests that tocilizumab could be an alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 18 publications
0
17
0
2
Order By: Relevance
“…Case reports have shown TCZ to be effective for a variety of other diseases, including autoimmune hemolytic anemia [ 171 , 172 ], reactive arthritis [ 173 ], autoimmune encephalitis [ 174 , 175 ], myasthenia gravis [ 176 ], Blau syndrome [ 177 ], anti-Caspre2 syndrome [ 178 ], refractory organizing pneumonia associated with Sjögren’s syndrome [ 179 ], cancer-related cachexia [ 180 ] and steroid refractory immune-mediated adverse events secondary to immune check point inhibitors [ 181 ]. Besides large vessel vasculitis, several case reports have indicated that TCZ has effects on rheumatoid vasculitis [ 182 ], polyarteritis nodosa [ 183 , 184 ], microscopic polyangiitis [ 185 , 186 ] and cryoglobulinemia vasculitis [ 187 ].…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…Case reports have shown TCZ to be effective for a variety of other diseases, including autoimmune hemolytic anemia [ 171 , 172 ], reactive arthritis [ 173 ], autoimmune encephalitis [ 174 , 175 ], myasthenia gravis [ 176 ], Blau syndrome [ 177 ], anti-Caspre2 syndrome [ 178 ], refractory organizing pneumonia associated with Sjögren’s syndrome [ 179 ], cancer-related cachexia [ 180 ] and steroid refractory immune-mediated adverse events secondary to immune check point inhibitors [ 181 ]. Besides large vessel vasculitis, several case reports have indicated that TCZ has effects on rheumatoid vasculitis [ 182 ], polyarteritis nodosa [ 183 , 184 ], microscopic polyangiitis [ 185 , 186 ] and cryoglobulinemia vasculitis [ 187 ].…”
Section: Therapeutic Targeting Of Il-6 In Diseasesmentioning
confidence: 99%
“…In refractory organising pneumonia, immunosuppressive agents such as azathioprine, cyclosporine, infliximab and rituximab have been used [113]. Recently, one case of refractory organising pneumonia was treated by tocilizumab with good efficacy [114].…”
Section: Organising Pneumonitismentioning
confidence: 99%
“…Series of OP associated with rheumatoid arthritis have described good results when treated with methotrexate, cyclophosphamide and azathioprine [24]. Others series show that tocilizumab could be a therapeutic alternative in refractory OP associated with systemic lupus erythematosus (SLE) [23, 25]. Relapses are common upon corticosteroid dose reduction or treatment suspension, thus often leading to prolonged treatment [2628].…”
Section: Discussionmentioning
confidence: 99%